Dari Literasi ke Investasi: Milenial, Gen Z, dan Transformasi Digital SBN Ritel - Raisa Maulida; Bella Aisya Ayu Aprilia; Hasto Prabowo Santoso; Yulia Asria Setyowati (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The trend of retail government securities investment among the younger generation (millennials and Generation Z) continues to grow. Fintech platforms make investment easier and safer. However, many millennials and Generation Z remain hesitant to invest in retail government securities due to a lack of information and inhibiting factors. This study examines the relationship between digital financial literacy and perceptions of fintech on retail government securities investment interest by considering the driving and inhibiting factors for millennials and Generation Z to invest in retail government securities. The results, processed using quantitative descriptive analysis and statistical analysis, indicate that the younger generation is the primary driver of the increase in retail government securities investors. Respondent characteristics, which align with national trends, indicate that investment interest is already high and supported by adequate financial literacy. However, further education is needed to foster this interest and translate it into actual purchases.